2016
DOI: 10.1186/s13027-016-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotypes distribution among Gabonese women with normal cytology and cervical abnormalities

Abstract: BackgroundCervical cancer is one of the most common tumors affecting women with a disproportionate mortality occurring in developing countries. Despite the high prevalence of cervical cancer and cervical neoplasia in Gabon, few studies have been performed to evaluate the prevalence and determinants of HPV infection in this country. The aim of this study was to determine the HPV prevalence and distribution in a population of Gabonese women with normal cytology and cervical abnormalities.MethodsA total of 200 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
(48 reference statements)
2
17
1
9
Order By: Relevance
“…Considering women with normal cervical cytology, when we compared the overall HPV prevalence among Tunisian women with that from neighboring Northern African countries, we reported that it was higher than that of Algeria (5.3%) [22], but lower than that of Morocco (34.3%) [30]. Additionally, we found relatively high HPV prevalence compared to Arab-Muslim countries from the Middle-East [3133] but substantially lower than that reported by other studies of the Sub-Saharan countries [34, 35] and Mediterranean Europe [36, 37]. The different origins and characteristics of the studied population (age, lifestyle, and ethnicity) may be the reason of these disparities in HPV prevalence.…”
Section: Discussioncontrasting
confidence: 43%
“…Considering women with normal cervical cytology, when we compared the overall HPV prevalence among Tunisian women with that from neighboring Northern African countries, we reported that it was higher than that of Algeria (5.3%) [22], but lower than that of Morocco (34.3%) [30]. Additionally, we found relatively high HPV prevalence compared to Arab-Muslim countries from the Middle-East [3133] but substantially lower than that reported by other studies of the Sub-Saharan countries [34, 35] and Mediterranean Europe [36, 37]. The different origins and characteristics of the studied population (age, lifestyle, and ethnicity) may be the reason of these disparities in HPV prevalence.…”
Section: Discussioncontrasting
confidence: 43%
“…We found HPV16 in 19 (41.30%), HPV18 in 9 (19.57%), and HPV45 in 1 (2.17%) of HPV positive samples. Human papillomavirus16 and HPV18 had the highest frequencies in cervical cancer (22,41), which is similar to our result. Another result showed that the frequencies of HPV35 and HPV31 were the highest (32), which is inconsistent with our result.…”
Section: Discussionsupporting
confidence: 82%
“…Certain strains of HPV are associated with different risk levels of transformation into genital tract in both males and females (13,(15)(16)(17). High-risk HPV16 and HPV18, which are found in high frequencies in cervical cancer, account for approximately two-thirds of all cervical carcinomas worldwide (HPV16 as the most frequent type) (16)(17)(18)(19)(20)(21)(22). associated with an increased risk of cervical cancer development (23).…”
Section: Introductionmentioning
confidence: 99%
“…Honduras'ta Tabore ve arkadaşları %88.2, Hindistan'da Baskaran ve arkadaşları %84.3, Fas'ta Assoumou ve arkadaşları %76.9, Kore'de Kim ve arkadaşları %75, Litvanya'da Simanaviciene ve arkadaşları %67.6, Venezuela'da Corenti ve arkadaşları %62, Romanya'da Corneanu ve arkadaşları %61, Çin'de Jiang ve arkadaşları %39.4 oranında bulmuşlardır. Ülkemizde Ankara'da yapılan çalışmalardan, Ergünay ve arkadaşları %80, Dursun ve arkadaşları %52, Aydoğan ve arkadaşları %50, Mersin'de yapılan çalışmada Tezcan ve arkadaşları %35.4 oranında tespit etmişlerdir [8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Discussionunclassified
“…Assoumou ve arkadaşları LSIL sitolojili kadınlarda HR HPV prevalansını %87.5, Tabora ve arkadaşları %81, Corenti ve arkadaşları %68, Simanaviciene ve arkadaşları %55.2, Jiang ve arkadaşları %43.5 olarak bulmuşlardır. Ülkemizde ise Dursun ve arkadaşları LSIL sitolojili kadınlarda HR HPV prevalansını %27, Abike ve arkadaşları %26, Aydoğan ve arkadaşları %34.5, Tezcan ve arkadaşları %42.9, Beyazıt ve arkadaşları %62, Baskaran ve arkadaşları %65.7, Ergünay ve arkadaşları %100 oranında bulmuşlardır [8][9][10]12,13,15,[16][17][18][19][20][21] . HSIL sitolojili kadınlardaki %66.7'lik HR HPV prevalansı Aydoğan ve arkadaşlarının %7'lik Dursun ve arkadaşlarının %20'lik oranından yüksek, Tezcan ve arkadaşlarının %75'lik oranına yakın, Assoumou ve arkadaşlarının %100, Ergünay ve arkadaşlarının %100, Tabora ve arkadaşlarının %97, Corenti ve arkadaşlarının %95, Kim ve arkadaşlarının %96.7, Abike ve arkadaşlarının %91, Jiang ve arkadaşlarının %90, Baskaran ve arkadaşlarının %84.6, Beyazıt ve arkadaşlarının %83 ve Simaviciene ve arkadaşlarının %80.3 oranlarından düşük tespit edilmiştir [8][9][10][11][12][14][15][16][17][18][19][20][21] .…”
Section: Discussionunclassified